Bionic Research on Bird Feather for Drag Reduction. (February 2015) - Feng, Beibei; Chen, Darong; Wang, Jiadao; Yang, Xingtuan
To reduce friction drag with bionic method in a more feasible way, the surface microstructure of bird feather was analyzed attempting to reveal the biologic features responding to skin friction drag reduction. Then comparative bionic surface mimicking bird feather was fabricated through hot-rolling technology for drag reduction. The microriblet film was formed on a PVC substrate through a self-developed hot-rolling equipment. The bionic surface with micron-scale riblets formed spontaneously due to the elastic-plastic deformation of PVC in high temperature and high pressure environment. Comparative experiments between micro-structured bionic surface and smooth surface were performed in a wind tunnel to evaluate the effect of bionic surface on drag reduction, and significant drag reduction efficiency was obtained. Numerical simulation results show that microvortex induced in the solid-gas interface of bionic surface has the effect of shear stress reduction and the small level of an additional pressure drag resulting from pressure distribution deviation on bird feather like surface, hence reducing the skin friction drag significantly. Therefore, with remarkable drag reduction performance and simple fabrication technology, the proposed drag reduction technique shows the promise for practical applications.